2010
DOI: 10.1007/s11199-010-9913-0
|View full text |Cite
|
Sign up to set email alerts
|

Are Gender Differences in Self-Reported Rumination Explained by Women’s Stereotyping?

Abstract: Although Response Styles Theory posits gender differences in ruminative thought related to depression, evidence of these differences resides largely in self-report data, leading us to hypothesize that stereotyping may influence women's perceived rumination. In an online survey with 94 U.S. Midwestern college women and 74 men, the re-affirmed relationship between gender and rumination (such that women reported higher levels than men) was moderated by general stereotype acceptance and endorsement of traditional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 36 publications
1
1
0
Order By: Relevance
“…Our findings suggest that the aftermath of the high may be a time of greater self-recrimination for women than for men. This seems consistent with findings that women are prone to a ruminative style of responding to events (Nolen-Hoeksema and Jackson, 2001; Nolen-Hoeksema et al, 1993; Yoder and Lawrence, 2011). Rumination is considered less adaptive than cognitive reframing or active coping and has been shown to predict drinking in alcohol abusers (Caselli et al, 2010).…”
Section: Discussionsupporting
confidence: 91%
“…Our findings suggest that the aftermath of the high may be a time of greater self-recrimination for women than for men. This seems consistent with findings that women are prone to a ruminative style of responding to events (Nolen-Hoeksema and Jackson, 2001; Nolen-Hoeksema et al, 1993; Yoder and Lawrence, 2011). Rumination is considered less adaptive than cognitive reframing or active coping and has been shown to predict drinking in alcohol abusers (Caselli et al, 2010).…”
Section: Discussionsupporting
confidence: 91%
“…According to the ruminative response style theory of depression, women have been shown to be more likely to ruminate about the causes of their mood than men in the face of depression (31), and it has been suggested that this difference in response styles could explain, at least in part, the gender disparity in adult depression (22,(32)(33)(34). To ensure such inter-group difference is valid, and not reflecting an artifact of the instrument, it is necessary to confirm consistency of meaning for the scale's items between groups (35).…”
Section: Introductionmentioning
confidence: 99%